De Gruyter handbook of digital cultures / edited by Grant Bollmer, Katherine Guinness, Yigit Soncul. - Bollmer, Grant; Guinness, Katherine; Soncul, Yigit (De Gruyter contemporary social sciences handbooks ;, 2025)
As digital cultures becomes the dominant term used by many across a variety of intellectual fields to describe the social, aesthetic, and political impact of digital media, it is necessary to provide a reference volume that specifies and defines the bounds of scholarly debates and curricular outlines for an otherwise amorphous interdisciplinary space. This handbook provides a comprehensive reference for the varied methodologies, historical frames, and theoretical perspectives essential for the study of digital cultures today. In outlining these foundations, it serves as a practical guide for educators and students into the broad range of perspectives grouped together for the critical, historical, and social scientific study of digital media.